4-Hydroxyisoleucine Alleviates Macrophage-Related Chronic Inflammation and Metabolic Syndrome in Mice Fed a High-Fat Diet - Yang, Jiali; Ran, Yunhui; Yang, Yonghui; Song, Shuyi; Wu, Yahong; Qi, Yuanming; Gao, Yanfeng; Li, Guodong (Frontiers in Pharmacology, 2021)
In obesity, macrophages and other immune cells accumulate in organs affected by insulin, leading to chronic inflammation and insulin resistance. 4-Hydroxyisoleucine (4-HIL) is a non-protein amino acid found in fenugreek seeds. 4-HIL enhances insulin sensitivity, but its mechanism is still unclear. In this study, 4-HIL intervention reduced weight gain, liver steatosis, and dyslipidemia; moreover, it increased systemic insulin sensitivity and improved insulin resistance in mice. Importantly, after administration, the accumulation of M1 like CD11c+ macrophages and inflammation in the liver and adipose tissue were reduced in the mice. 4-HIL also reduced the proportion of CD11c+ macrophages among bone marrow-derived macrophages, which were induced in vitro. These observations demonstrate a new role of 4-HIL in insulin resistance in hepatocytes and adipocytes. 4-HIL inhibits obesity-related insulin resistance by reducing inflammation and regulating the state of M1/M2 macrophages.